Evolution of Molecularly Imprinted Enzyme Inhibitors: From Simple Activity Inhibition to Pathological Cell Regulation. Issue 46 (11th October 2021) - Xu, Jingjing; Miao, Haohan; Zou, Lihua; Tse Sum Bui, Bernadette; Haupt, Karsten; Pan, Guoqing
Abstract: Molecular imprinting represents one of the most promising strategies to design artificial enzyme inhibitors. However, the study of molecularly imprinted enzyme inhibitors (MIEIs) remains at a primary stage. Advanced applications of MIEIs for cell regulation have rarely been explored. Using a solid‐phase oriented imprinting strategy so as to leave the active site of the enzymes accessible, we synthesized two MIEIs that exhibit high specificity and potent inhibitory effects (inhibition constant at low nM range) towards trypsin and angiogenin. The trypsin MIEI inhibits trypsin activity, tryptic digestion‐induced extracellular matrix lysis and cell membrane destruction, indicating its utility in the treatment of active trypsin‐dependent cell injury. The angiogenin MIEI blocks cancer cell proliferation by suppressing the ribonuclease activity of angiogenin and decreasing the angiogenin level inside and outside HeLa cells. Our work demonstrates the versatility of MIEIs for both enzyme inhibition and cell fate manipulation, showing their great potential as therapeutic drugs in biomedicine. Abstract : Molecularly imprinted enzyme inhibitors (MIEIs) were tailored for the inhibition of trypsin‐induced cell injury and angiogenin‐induced cancer cell proliferation, demonstrating their great potentials as therapeutic drugs for disease treatment.